Tick immunity using mRNA, DNA and protein-based Salp14 delivery strategies. Issue 52 (20th December 2021) - Matias, Jaqueline; Kurokawa, Cheyne; Sajid, Andaleeb; Narasimhan, Sukanya; Arora, Gunjan; Diktas, Husrev; Lynn, Geoffrey E.; DePonte, Kathleen; Pardi, Norbert; Valenzuela, Jesus G.; Weissman, Drew; Fikrig, Erol
Abstract: Guinea pigs exposed to multiple infestations with Ixodes scapularis ticks develop acquired resistance to ticks, which is also known as tick immunity. The I. scapularis salivary components that contribute to tick immunity are likely multifactorial. An anticoagulant that inhibits factor Xa, named Salp14, is present in tick saliva and is associated with partial tick immunity. A tick bite naturally releases tick saliva proteins into the vertebrate host for several days, which suggests that the mode of antigen delivery may influence the genesis of tick immunity. We therefore utilized Salp14 as a model antigen to examine tick immunity using mRNA lipid nanoparticles (LNPs), plasmid DNA, or recombinant protein platforms. salp14 containing mRNA-LNPs vaccination elicited erythema at the tick bite site after tick challenge that occurred earlier, and that was more pronounced, compared with DNA or protein immunizations. Humoral and cellular responses associated with tick immunity were directed towards a 25 amino acid region of Salp14 at the carboxy terminus of the protein, as determined by antibody responses and skin-testing assays. This study demonstrates that the model of antigen delivery, also known as the vaccine platform, can influence the genesis of tick immunity in guinea pigs. mRNA-LNPs may be useful in helping to elicit erythema at the tick bite site, one of the most important early hallmarks of acquired tick resistance. mRNA-LNPs containing tick genes is a useful platform for the development of vaccines that can potentially prevent selected tick-borne diseases.